Middle Sulawesi in Dealing With Free Trade Through The ASEAN Economic Community (AEA) - Husain, Sulfitri (Jurnal Ilmu Hubungan Internasional LINO, 2022)
The ASEAN Economic Community (AEC) is still ongoing, for Indonesia, especially Middle Sulawesi, the formation of an integrated economic area in Southeast Asia is an opportunity as well as an obstacle that must be faced. From the aspect of opportunity, AEC makes everything easier, including more open economic activities and various opportunities with a free trade platform. However, from another aspect, the lack of quality human resources and inadequate infrastructure are obstacles for middle Sulawesi which is still improving. From these two aspects, this study aims to determine the extent of the opportunities and obstacles faced by middle Sulawesi in dealing with free trade through the ASEAN Economic Community (AEC). This paper uses a descriptive qualitative method. Secondary data is used as the basis for descriptive analysis. The results of this study indicate that middle Sulawesi has the opportunity to conduct free trade by looking at its strategic geographical location and abundant natural resources. However, in addition to the opportunities it has, this province also has several obstacles which of course must receive attention for the sake of sustainable development while strengthening the competitiveness of Central Sulawesi Province. The next agenda that must be carried out by the government is to pay attention to and improve the factors that become obstacles to free trade, especially from several prioritized sectors including human resources and infrastructure.